Social Justice for a democratic and equitable international order - Alfred de Zayas (Revista Tecnológica)
This article reviews key substantive issues addressed by main ongoing global policy processes with a particular focus on the Second World Summit for Social Development (WSSD2) and the Global Coalition on Social Justice. These issues include the Right to Development as a core principle underlying social development and the realization of social justice and development in terms of international law standards. The article identifies and assesses relevant international law, policy formulations, expertise, and political processes to demonstrate their bearing on the WSSD2 and global discussion of social justice. This approach is intended to bridge academic exercise with briefing guidance for Social Justice and development actors. Core building blocks are identified: human rights codification and social responsibility; transforming the Rule of Law into the Rule of Justice; and imperatives for enforcement of United Nations Treaties, judgments and resolutions. Also, UN texts on the Right to Development and the Right to International Solidarity; the Summit of the Future and the BRICS Summit 2024; and norms and expectations of international cooperation are analysed herein. Conclusions posit that the Right to Development must be seen as juridical, justiciable and enforceable. Finally, the article recommends that the content and outcome of the WSSD2 and other global processes need to redress the paradigm by reaffirming international legal obligations and casting social justice development in terms of international law, the existing human rights treaty system, formal UN Declarations, disarmament for development.